2019
DOI: 10.1021/acs.energyfuels.9b02300
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Initial Gel Fuel Temperature on the Ignition Mechanism and Characteristics of Oil-Filled Cryogel Droplets in the High-Temperature Oxidizer Medium

Abstract: The ignition mechanism was studied for a group of gel fuel compositions in a high-temperature oxidizer medium. It was determined how the initial temperature of the fuel influences the ignition characteristics. The gel fuel (oil-filled cryogel) was prepared from an oil emulsion based on the mixture of a combustible liquid and polyvinyl alcohol. The composition of primary oil emulsions was as follows: the aqueous solution of polyvinyl alcohol (5, 10 wt %) + 40–60 vol % of oil + 2 vol % of emulsifier. The initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…As a result of the numerical modeling of the process being researched, the ignition delay times of the gel fuel were obtained. These values are in satisfactory agreement with the corresponding experimental data in [33] (Figure 4) where the temperature T varies between 973 and 1273 K, and the initial fuel temperature equals 203 K. The difference between the theoretical and experimental values of ignition delay times does not exceed the measurement error τ in the experiments in [33]. Based on the satisfactory agreement between the results of the mathematical simulation and the experimental data in [33], it can be concluded that the developed mathematical model adequately describes a group of interdependent physicochemical processes taking place during the ignition of gel fuel in a high-temperature environment.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As a result of the numerical modeling of the process being researched, the ignition delay times of the gel fuel were obtained. These values are in satisfactory agreement with the corresponding experimental data in [33] (Figure 4) where the temperature T varies between 973 and 1273 K, and the initial fuel temperature equals 203 K. The difference between the theoretical and experimental values of ignition delay times does not exceed the measurement error τ in the experiments in [33]. Based on the satisfactory agreement between the results of the mathematical simulation and the experimental data in [33], it can be concluded that the developed mathematical model adequately describes a group of interdependent physicochemical processes taking place during the ignition of gel fuel in a high-temperature environment.…”
Section: Resultssupporting
confidence: 91%
“…For time discretization, a step of 10 −3 s was used. This step corresponded to the accuracy of the experiment [33], the data of which were used in this work.…”
Section: Dominance Of Conductive Heat Flux On the Surface Of A Gel Fuel Samplementioning
confidence: 99%
“…Gel fuels filled with composite particles possess the enhanced rheo-physical property and better performance of combustion and explosion [1][2][3], such as higher combustion rates [4,5] and catalytic decomposition [6,7]. These benefits allow gel fuels to be used for a wider range of advanced propulsion systems.…”
Section: Introductionmentioning
confidence: 99%